An Epidemiological Study of Homicidal Cases Autopsied in the Mortuary of the Department of Forensic Medicine and Toxicology, North Bengal, Darjeeling - Achintya Biswas; Pappu Kumar; Sukanta Majumdar; Soumeek Chowdhuri; Somasish Ghosal; Prabir Kumar Deb (Institute of Medico-legal Publications Pvt Ltd, 2021)
Homicide is regarded as a notorious crime against the society that causes intentional killing, aggravatedassaults resulting in death. This brings a massive burden on national economies, law enforcement and lostproductivity. The present study highlighted the epidemiological profile of homicidal deaths which accounted(3.9%) of all unnatural deaths autopsied. Overall trend shows high male predominance with low economicbackground where illiteracy, poverty and other social circumstances play a considerable role. Homicidalrecords have their importance in interpretation of socio-economic implications and overall administrativeattributes on executing law and order in respect to time, place and conditions.